2023
DOI: 10.31234/osf.io/t2c9a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No foreign language effect in incentivized gambles with verbal probability expressions

Abstract: The Foreign Language effect is claimed to decrease risk aversion. We found no such effect. First, we asked N = 229 Polish native speakers to assign numerical values to verbal probability phrases in Polish and English. After finding very few differences, we conducted an incentivized experiment, N = 281, where Poles had to decide whether they would prefer to receive a granted amount of money or take part in a lottery task where the chance of winning was expressed by the phrases from the pre-test. Regardless of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As the research on the foreign language effect progresses, the effect appears more complex and malleable than initially hoped. For example, we found no foreign language effect on risky choice ( Borkowska et al 2023 ; Muda et al 2020 ) and using a foreign language has been shown to distort the ability to delay gratifications ( Białek et al 2022 ), reason logically ( Białek et al 2020 ) or the ability to discern true from false news ( Muda et al 2023 ). Numerous studies from other labs are also reporting no effects of using a foreign language on decision-making.…”
Section: The Foreign Language Effectmentioning
confidence: 67%
“…As the research on the foreign language effect progresses, the effect appears more complex and malleable than initially hoped. For example, we found no foreign language effect on risky choice ( Borkowska et al 2023 ; Muda et al 2020 ) and using a foreign language has been shown to distort the ability to delay gratifications ( Białek et al 2022 ), reason logically ( Białek et al 2020 ) or the ability to discern true from false news ( Muda et al 2023 ). Numerous studies from other labs are also reporting no effects of using a foreign language on decision-making.…”
Section: The Foreign Language Effectmentioning
confidence: 67%